2011
DOI: 10.1002/cncr.26587
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling is a potential diagnostic tool for thyroid cancer

Abstract: BACKGROUND: Approximately 30% of fine‐needle aspiration (FNA) biopsies of thyroid nodules are indeterminate or nondiagnostic. Recent studies suggest microRNA (miRNA, miR) is differentially expressed in malignant tumors and may have a role in carcinogenesis, including thyroid cancer. The authors therefore tested the hypothesis that miRNA expression analysis would identify putative markers that could distinguish benign from malignant thyroid neoplasms that are often indeterminate on FNA biopsy. METHODS: A miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 27 publications
(36 reference statements)
3
111
0
1
Order By: Relevance
“…The expression of MiR-125b in cancers is controversial. Some studies have shown that MiR-125b is upregulated or downregulated in different cancers under pathophysiological conditions [16][17][18][19]. Although our previous study reported that MiR-125b was upregulated 4.88-fold in gastric cancer [20], the expression level and biological impact of MiR-125b in gastric cancer were never well studied.…”
Section: Discussionmentioning
confidence: 85%
“…The expression of MiR-125b in cancers is controversial. Some studies have shown that MiR-125b is upregulated or downregulated in different cancers under pathophysiological conditions [16][17][18][19]. Although our previous study reported that MiR-125b was upregulated 4.88-fold in gastric cancer [20], the expression level and biological impact of MiR-125b in gastric cancer were never well studied.…”
Section: Discussionmentioning
confidence: 85%
“…Ascertaining the origin and development of liver cancer and identification of novel targets for therapy have been the focus of recent studies regarding HCC (3)(4)(5)(6)(7). MicroRNAs (miRs) are single-stranded noncoding RNAs, containing 17-19 nucleotides, which are associated with the development and progression of tumors (8)(9)(10)(11)(12) such as oropharyngeal squamous cell carcinoma (8), non-small cell lung cancer (9), thyroid cancer (10). miR-125a has previously been reported to block the proliferation, invasion and migration of breast cancer cells (13), and was also found to be effective in preventing the invasion of ovarian cancer (14), glioma (15), lung cancer (16)(17)(18) and gastric cancer (19).…”
Section: Introductionmentioning
confidence: 99%
“…The results did not comprise a merging of the expression levels of all the evaluated miRNAs, which may have improved the diagnostic potential. Along the same vein, a comprehensive study by Vriens et al (2012) (miR-100, miR-125b, miR-138 and miR-768-3p were up-regulated in the malignant entities). Subsequent QRT-PCR analysis of the specific miRNAs revealed miR-138 to be differentially expressed between benign and malignant FNAs (P!0.001) and an ultimate diagnostic accuracy of 75% and NPV of 81%.…”
Section: Mrna-based Classification Modelsmentioning
confidence: 92%